Homogeneous photometry – VII. Globular clusters in the Gaia era. Issue 3 (2nd March 2019) - Stetson, P B; Pancino, E; Zocchi, A; Sanna, N; Monelli, M
ABSTRACT: We present wide-field, ground-based Johnson–Cousins UBVRI photometry for 48 Galactic globular clusters based on about 90 000 public and proprietary images. The photometry is calibrated with the latest transformations obtained in the framework of our secondary standard project, with typical internal and external uncertainties of order a few millimagnitudes. These data provide a bridge between existing small-area, high-precision HST photometry and all sky catalogues from large surveys like Gaia, SDSS, or LSST. For many clusters, we present the first publicly available photometry in some of the five bands (typically U and R ). We illustrate the scientific potential of the photometry with examples of surface density and brightness profiles and of colour–magnitude diagrams, with the following highlights: (i) we study the morphology of NGC 5904, finding a varying ellipticity and position angle as a function of radial distance; (ii) we show U -based colour–magnitude diagrams and demonstrate that no cluster in our sample is free from multiple stellar populations, with the possible exception of a few clusters with high and differential reddening or field contamination, for which more sophisticated investigations are required. This is true even for NGC 5694 and Terzan 8 that were previously considered as (mostly) single-population candidates.